Determination of the branching fractions of B0S→ D∓SK∓ and B0 → D-SK+ - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Journal of high energy physics, 2015)
Measurements are presented of the branching fractions of the decays BS0→ DS∓K∓ and B0 → DS−K+ relative to the decays BS0→ DS−π+ and B0 → D−π+, respectively. The data used correspond to an integrated luminosity of 3.0 fb−1 of proton-proton collisions. The ratios of branching fractions areℬBs0→Ds∓K∓ℬBs0→Ds−π+=0.0752±0.0015±0.0019$$ \frac{\mathrm{\mathcal{B}}\left(B_{s}^0→ D_{s}^{\mp }{K}^{\mp}\right)}{\mathrm{\mathcal{B}}\left(B_{s}^0→ D_{s}^{-}{π}^{+}\right)}=0.0752± 0.0015± 0.0019